SYNTHESIS AND ANALGESIC ACTIVITY OF 6-(MNITROPHENYL)-4-SUSTITUTED BENZYLIDENE-4,5-DIHYDROPYRIDAZIN-3(2H)-ONE DERIVATIVES - Asif, Mohammad (Indonesian Journal of Pharmacy, 2012)
Many  research  groups  have  been  interested  in  3(2H)-pyridazinones  for  the  development  of  potential  analgesic  and  antiinflammatory  agents.  Stimulated  by  these  findings,  three  6-(mNitrophenyl)-4-sustituted  benzylidene-4,5-dihydropyridazin-3(2H)-ones (IVa-IVc) have been synthesized and evaluated for analgesic activity  against  hot  plate  method.  Compounds IVa-IVc were prepared from 6-m-nitrophenyl-4,5-pyridazin-3(2H)-one by condensation  with  respective  aldehydes.  All  compounds  (IVa-IVc)  having nitro  phenyl  and  benzylidene  groups  at  position  6  and  4  of  the pyridazinone  ring  receptively.  All  compounds  (IVa-IVc)  showed significant  analgesic  activity  when  compare  to  control  group  and were found less potent than reference drug aspirin.Key words:Pyridazinones, analgesic, benzylidene, nitrophenyl.